APATITE LUMINESCENCE - Waychunas G.A. (My University, 2002)
Apatite group minerals are among the most interesting of luminescent minerals due to their wonderful combinations of varying emission color, complex zoning, and intriguing associations. Several of the most famous mineral localities known for spectacularly fluorescent mineral associations involve apatite group minerals, calcite and ore minerals. For example, Långban, Sweden, with svabite, hedyphane and mimetite; and Franklin, New Jersey, USA, with fluorapatite, svabite and turneaurite (see e.g., Bostwick 1977, Robbins 1994). Apatite is also an extremely common mineral, formed under a wide range of conditions and in many types of host rock. The diversity of its luminescence is...